A Correlation Exists Between Subchondral Bone Mineral Density of the Distal Radius and Systemic Bone Mineral Density - Rhee, Seung Hwan (Springer-Verlag, 2011)
BACKGROUND: Intraarticular distal radius fractures are common and risk articular congruity owing to disruption of the subchondral bone. Studies regarding microstructure and mechanical properties of the distal radius, however, focus only on the cortical and trabecular bones in the metaphysis and not on the subchondral bone. QUESTIONS/PURPOSES: This study was conducted to (1) quantify the regional bone mineral density of the subchondral plate in the distal radius; (2) analyze the topographic distribution pattern of the subchondral bone mineral density; and (3) evaluate the correlation between the subchondral bone mineral density and the potentially related clinical factors of age, height, weight, BMI, systemic bone mineral densities, socio-occupational classification, and hand osteoarthritis grading. METHODS: Eighty postmenopausal women with a mean age of 68 years (range, 52–88 years) were enrolled in this study. Digital images of the distal radii of the subjects were scanned by conventional CT and processed to provide the regional bone mineral density of the subchondral plate using a CT osteoabsorptiometry technique. The estimated subchondral bone mineral density was analyzed to evaluate the topographic pattern and its correlation with various clinical factors, including age, height, weight, BMI, degree of hand osteoarthritis, socio-occupational class, and systemic bone mineral density measured in the lumbar spine and hip. RESULTS: During topographic analysis of a densitometric map, a bicentric distribution of the subchondral bone mineral density was found. Among the clinical factors, only the systemic bone mineral density measured by dual-energy x-ray absorptiometry in the femur neck and lumbar spine had a significant correlation with the subchondral bone mineral density of the distal radius. CONCLUSION: Systemic bone mineral density correlates substantially with the subchondral bone mineral density of the distal radius as a constitutional factor, whereas other local factors arising from the gravitational load or joint reaction force are not associated with the subchondral bone mineral density of the distal radius. LEVEL OF EVIDENCE: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.